Peran Budaya Organisasi Dan Kepemimpinan Transformasional Dalam Meningkatkan Komitmen Afektif Dan Kinerja Perawat - Tetik Nurhayati; Novi Enis Rosuliana; Kusmiyati; Anah Sasmita; Peni Cahyati (Jurnal Kesehatan Mahardika, 2026)
A robust organizational culture combined with transformational leadership significantly contributes to nurses forming a strong emotional bond with their workplace. This research aims to explore and assess the influence of organizational culture and transformational leadership style on nurses' emotional attachment and job performance in hospital wards. The outcomes of this study can guide hospitals in enhancing nurses' work in patient care settings. Employing a descriptive method alongside verification analysis, the study collects and verifies data. Data collection was conducted through a questionnaire, and proportional random sampling was used to select 189 participants. Path analysis was utilized for data examination. Descriptive analysis results reveal that organizational culture, transformational leadership, affective commitment, and nurse performance in inpatient units range from poor to good. Verification analysis results show that both organizational culture and transformational leadership simultaneously impact affective commitment. Additionally, affective commitment influences nurses' job performance. It was found that organizational structure and leadership style, particularly transformational leadership, enhance nurses' performance by fostering a stronger emotional connection to their work.